2019
DOI: 10.1051/medsci/2019168
|View full text |Cite
|
Sign up to set email alerts
|

Télédent, une expérience de téléexpertise bucco-dentaire en milieu pénitentiaire

Abstract: La santé bucco-dentaire participe au maintien d’un bon état général de l’organisme. Certaines populations, dont les personnes détenues, ont des besoins importants mais, simultanément, un accès limité aux soins dentaires. Télédent est un outil complémentaire de téléexpertise bucco-dentaire qui facilite le dépistage et la prévention des troubles oraux. À partir d’une caméra intra-buccale qui enregistre des images qui sont analysées par l’équipe du service de médecine bucco-dentaire de l’Hôpital Henri Mondor, l’U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…However, these values were relatively low when comparing the teledentistry examination by the PHV and direct oral examination by the dentist. The first study using oral teleconsultation in a prison was performed by Giraudeau et al [ 5 ] and several studies have utilized the IOC in teletedentistry for oral examination of prisoners [ 5 , 17 , 18 ]. However, to our knowledge, our study is the first to assess the validity, regarding sensitivity and specificity, of using teledentistry for dental disease screening in comparison to the direct oral examination by a dentist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these values were relatively low when comparing the teledentistry examination by the PHV and direct oral examination by the dentist. The first study using oral teleconsultation in a prison was performed by Giraudeau et al [ 5 ] and several studies have utilized the IOC in teletedentistry for oral examination of prisoners [ 5 , 17 , 18 ]. However, to our knowledge, our study is the first to assess the validity, regarding sensitivity and specificity, of using teledentistry for dental disease screening in comparison to the direct oral examination by a dentist.…”
Section: Discussionmentioning
confidence: 99%
“…In the present teledentistry program, the IOC was used due to its low cost, being convenient to transport, and easy to maintain. The IOC has been used for patient-dentist communication [ 5 , 22 ], oral examination [ 17 , 18 ], screening oral cancer lesions [ 23 ], and identifying dental diseases and soft tissue conditions [ 21 , 24 ]. Previous studies have found that the IOC is a valid and reliable tool for screening oral diseases, such as dental caries [ 21 ] and oral cancer [ 23 ], compared with a direct oral examination.…”
Section: Discussionmentioning
confidence: 99%
“…The development of good working relationships with prison staff supported the practical elements of delivering the intervention in a number of studies 24,25 . In the case of teledentistry, prison health staff trained in teledentistry recorded the teleconsultation for a dental professional to review remotely 25 . In the study conducted by Grey and Fawcett, prison nurses carried out the dental triaging protocol 23 …”
Section: Question 2: What Were the Barriers And Facilitators To Imple...mentioning
confidence: 99%
“…Three studies involved teledentistry in screening of prisoners for dental treatment needs on their admission to prison. [24][25][26] All studies were conducted in France, two of which were carried out in the same prison. 24,26 The interventions involved a nurse in the prison using an intraoral camera and fluorescent light to record the mouth of the prisoner for asynchronous review by a remote dentist.…”
Section: Teledentistrymentioning
confidence: 99%
See 1 more Smart Citation